Viver e contar: “Espaço Autoficcional” como lugar de encontro na obra de Salim Miguel - Silva, Ana Cláudia de Oliveira da (2018)
The present work consists of a study of the fictional work of Salim Miguel, centered in the different figurative strategies used to blur the boundaries between life and work. More than an autobiographical and/or narcissistic gesture, this support that the writer seeks in vestiges, traces and fragments of his own past to create fictionally relates fundamentally to his aesthetic-literary conception: fiction as a re-creation in another universe, formed entirely by words, of an experience, known or lived. Literary writing is thus characterized as a kind of inter-place, which enables Salim Miguel to constantly come and go between the "reality of life" and the "reality of fiction", phenomena which, in his view, merge and become confused. In order to reflect on how this happens, were selected six representative works: A morte do tenente e outras mortes (1979), A vida breve de Sezefredo das Neves, poeta (1987), Primeiro de abril: narrativas da cadeia (1994), Onze de Biguaçu mais um (1997), Nur na escuridão (1999) and Reinvenção da Infância (2009). In such narratives, we identify these aspects that point to the urgent need to discuss the uncomfortable presence of the author in his text, reactivated in contemporary times by the concepts of self-fiction, "return of the author" and "biographical space”. From this analytical perspective, the objective of this work is to discuss the creation of a "self-made space" in Salim Miguel's work as a meeting place of the fictionist/collector with his own experience and, also, a place of re-creation of this threshold experience between the "act of living" and the "counting act".